Spiritual Assessment within Clinical Interventions Focused on Quality of Life Assessment in Palliative Care: A Secondary Analysis of a Systematic Review - Catania, Gianluca (Religions, 2016)
One of the most crucial palliative care challenges is in determining how patients' needs are defined and assessed. Although physical and psychological needs are commonly documented in patient's charts, spiritual needs are less frequently reported. The aim of this review was to determine which explicit, longitudinal documentation of spiritual concerns would sufficiently affect clinical care to alleviate spiritual distress or promote spiritual wellbeing. A secondary analysis of a systematic review originally aimed at appraising the effectiveness of complex interventions focused on quality of life in palliative care was conducted. Five databases were searched for articles reporting interventions focused on QoL including at least two or more QoL dimensions. A narrative synthesis was performed to synthesize findings. In total, 10 studies were included. Only three studies included spiritual wellbeing assessment. Spirituality tools used to assess spiritual wellbeing were different between studies: Hospital QoL Index 14; Spiritual Needs Inventory; Missoula-Vitas QoL Index; and the Needs Assessment Tool: Progressive Disease-Cancer. Only one study reported a healthcare professional's session training in the use of the QoL tool. Two out of three studies showed in participants an improvement in spiritual wellbeing, but changes in spiritual wellbeing scores were not significant. Overall patients receiving interventions focused on QoL assessment experienced both improvements in their QoL and in their spiritual needs. Although spiritual changes were not significant, the results provide evidence that a spiritual need exists and that spiritual care should be appropriately planned and delivered. Spiritual needs assessment precedes spiritual caring. It is essential that interventions focused on QoL assessment in palliative care include training on how to conduct a spiritual assessment and appropriate interventions to be offered to patients to address their spiritual needs.